The productivity effects of stock option schemes: Evidence from Finnish panel data - Derek C. Jones; Panu Kalmi; Mikko Mäkinen (The Research Institute of the Finnish Economy (ETLA), 2006)
While theorists differ sharply on the expected economic impact of stock options, typically empirical work has found a positive association between option schemes and firm productivity. However, existing data are limited and may not enable reliable investigation of the productivity effects of different types of option scheme. New panel data for all Finnish publicly listed firms during 1992-2002 enable us to distinguish plans that are broad based and others limited to particular employees and address issues of endogeneity concerning inputs and options. Diverse specifications are estimated including dynamic panel data models with a GMM estimator. For broad-based option scheme indicators the key result is that different estimators consistently find statistically insignificant associations with firm productivity. For selective option schemes, the baseline fixed effects estimator suggests a 2.1-2.4% positive and statistically significant effect of a dilution indicator on firm productivity. However, in empirical models in which endogeneity and dynamics are taken into account, no evidence is found of a link with firm productivity. Thus our findings are consistent with hypotheses that predict negligible effects of option plans for enterprise performance, such as those based on free riding, or psychological expectancy theory or accounting myopia. However, by finding weak evidence for productivity effects of targeted schemes (and none for broad-based plans) our findings tend not to support hypotheses based on managerial rent seeking.
Keywords: M5; J3; L2; C3; 330; personnel economics; stock options; productivity; panel data; Leistungsorientierte Vergütung; Aktienoption; Wirtschaftlichkeit; Finnland